2012
DOI: 10.1007/s00264-012-1619-1
|View full text |Cite
|
Sign up to set email alerts
|

Time to internal fixation of femoral neck fractures in patients under sixty years—does this matter in the development of osteonecrosis of femoral head?

Abstract: Purpose Osteonecrosis of femoral head remains a major complication of femoral neck fractures. It has been postulated that early internal fixation drastically reduces the incidence of osteonecrosis of the femoral head. However, there is a paucity of literature looking at the effect of time delay to internal fixation on the development of this late complication. In this study, we aim to assess the effect of time delay and method of internal fixation on the development of osteonecrosis in those less than 60 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
57
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 24 publications
1
57
0
2
Order By: Relevance
“…With the change of diet (especially alcohol addiction), increase in traffic accidents (most result in femoral-neck fracture), and abuse of pain-killer drugs or immunosuppressive drugs (commonly glucocorticoids), and so on, the morbidity of ONFH presents an apparently rising tendency, and most are young and middle-aged patients [1][2][3]. If not treated in time, it will greatly affect the patient's life.…”
Section: Introductionmentioning
confidence: 99%
“…With the change of diet (especially alcohol addiction), increase in traffic accidents (most result in femoral-neck fracture), and abuse of pain-killer drugs or immunosuppressive drugs (commonly glucocorticoids), and so on, the morbidity of ONFH presents an apparently rising tendency, and most are young and middle-aged patients [1][2][3]. If not treated in time, it will greatly affect the patient's life.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism for the development of osteonecrosis of the femoral head is believed to be related to the stress generated from the formation of a hollow space after necrosis and the lack of mechanical support of the subchondral bone [18][19][20]. Therefore, based on this principle, researchers have designed a variety of support devices to mechanically support the femoral head and have achieved certain effects from devices such as the tantalum rod [21] and the titanium alloy support device [22].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary there are studies that found that the rates of non-union and avascular necrosis were not statistically different between those treated within 12 to 24 hours from the time of injury from those treated thereafter. [6][7][8]10 In our study we aim to address these disparities and study the effect of delayed fixation on union by reducing the confounding factors affecting the outcome. Patients treated with open reduction were also not included in this study.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 But other variables such as use of closed or open reduction, 8,9,15,16,17 the role of capsulotomy, [11][12][13]17 timing of surgery [4][5][6][7][8][9][10] and age group 60-70 years 17 still remains controversial. The method of fixation remains a less controversial variable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation